MATRIFOCALITY AND ITS IMPLICATION TO THE PRACTICE OF ISLAMIC FAMILY LAW IN THE PATRIARCHAL MUSLIM SOCIETY OF GAYO, INDONESIA - Arfiansyah, A; Amalia, Nanda; Widyanto, Anton (Universitas Islam Negeri Ar-Raniry, 2023)
Many scholars have studied matrifocality in Indonesia as a social system in a matrilineal community. Few observe matrifocality as a practice in a purely patriarchal society. This research examines emerging matrifocality in the pure patriarchal Gayo community of Aceh province. The emergence started with the invention of the coffee plantation, which led the Gayonese people to rearrange their social system and invent a new residential marriage pattern that led the matrifocality into practice. This research conducted some phases of fieldwork; intensive ethnographical fieldwork was conducted in 2014-2015, which was updated in 2018-2019 in Central Aceh and Bener Meriah districts. The standard qualitative method (interview and observation) was also applied to several Gayonese academicians and professionals living in Banda Aceh municipality, the capital of Aceh Province, to see the practice of Islamic family law in their families. This research found that the invention of economic sources prompted Gayonese people to migrate internally, which resulted in practicing neolocal marriage. This new marriage pattern started the matrifocality practice that set a new power relationship of the purely patriarchal society to a relatively equal one. This happened once with the increasing Islamization of the area. Instead of strengthening patriarchal tradition, it gives space for women to assert their role and rights over property equality with men.